To Thine Own Self Be True? Facades of Conformity, Values Incongruence, and the Moderating Impact of Leader Integrity - Hewlin, Patricia Faison; Dumas, Tracy L.; Burnett, Meredith Flowers (Academy of Management Journal, 2017)
When employees feel that their values do not match those of the organization, they often respond by pretending to fit in. We examine how leader integrity influences the tendency to create facades of conformity, proposing that employees will actually fake more when leaders are principled. In a laboratory experiment (Study 1), undergraduate students whose values ostensibly differed from those of other discussion group members and the university administration created more facades when they perceived the discussion group leader as having high integrity. A two-wave survey of employed adults (Study 2) replicated the moderation effect and also revealed negative effects of facade creation on work engagement. In both studies, our results indicate that, ironically, when leader integrity is high, the tendency to create facades of conformity in response to low values congruence is magnified. Additionally, our findings reveal that positive attributes in leaders may not always result in positive responses from followers. The results from our study also show that facades of conformity may serve as a partial explanatory mechanism in the relationship between values congruence and employee engagement.